Collecting Site‐Level Data on Organisms Causing Surgical Site Infections to Guide Quality Improvement. (31st March 2021) - Goldman, Lauren; McAlister, Sarah A.; Keith, Abigail; Bone, Nathalie; McSwain, Jenna M.; Klineline, Dena N.; Hagedorn Wonder, Amy
ABSTRACT: Surgical site infections (SSIs) negatively affect patients and health care organizations. We conducted a descriptive, correlational study at two hospitals that provide care to rural patients in one Midwestern state. The study purposes were to describe: types of organisms causing reportable organ/space SSIs that occurred within 30 days of an open or a laparoscopic abdominal surgery (N = 20), and commonalities in patient‐ and care‐related factors to provide baseline information for site‐level prevention efforts for quality improvement. We identified Escherichia coli in almost half of the SSI cases (n = 9, 45%). Common patient‐related factors included ethnicity, smoking, and dirty or contaminated wounds. Common care‐related factors included longer surgery times (> 60 minutes), unplanned surgeries, and procedures that involved the colon or small bowel. Personnel can use site‐level data to monitor prevalent types of organisms causing SSIs, enabling an evidence‐based, interdisciplinary approach to develop and test methods to enhance prevention.